Pengaruh Online Customer Review Dan Rating Terhadap Kepuasan Konsumen Pada Aplikasi Pt. Bfi Finance Indonesia Tbk Cabang Karawang - Yunita Eka Sari; Citra Savitri; Syifa Pramudita Faddila (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Currently online customer reviews and ratings on the BFI Finance application have negative reviews of BFI Finance related to consumer complaints, this is a big challenge faced by the company to create a positive corporate image and satisfy consumers with this service. Therefore, companies need to have consumer understanding when purchasing, using and evaluating services to meet consumer demand and satisfaction. This study aims to examine the effect of online customer reviews and ratings on consumer satisfaction in PT. BFI Finance Indonesia Tbk Karawang Branch. In this study, a quantitative descriptive verification approach was used and data analysis was applied using Path Analysis. The population of this research is active consumers of BFI Finance, Karawang Branch, who use loan products with a total of 7101 people with a sample of 380 respondents. The results of this study prove that the correlation between the two online customer review and rating variables has a close and positive relationship which shows a strong and unidirectional correlation. and online customer reviews have a partially significant effect on customer satisfaction and similarly ratings have a partially significant effect on customer satisfaction. In addition, it was also found that the simultaneous (simultaneous) effect of online customer reviews and ratings on consumer satisfaction is also significant. Keywords: online customer review, rating, customer satisfaction